Immigrants in Finland as a Problem Discussed in Leena Lehtolainen’s Minne Tytöt Kadonneet - Kokotkiewicz, Martyna (Folia Scandinavica Posnaniensia, 2014)
Leena Lehtolainen belongs to the most appreciated Finnish authors of crime fiction. One of the significant features of her works is that she discusses some most alarming social issues in them. The problem concerning immigration and its different aspects can definitely be considered as an example of such an issue. Since the problem of cultural antagonisms, racial hatred and xenophobia has been widely discussed by many other Scandinavian authors of crime fiction as well, it is worth analyzing how Lehtolainen herself approaches the problem. The aim of this article is to discuss some aspects concerning the problems of immigrant societies in Finland, basing on one of Leena Lehtolainen’s novels, Minne tytöt kadonneet, which main subject could be described as a collision of two completely different cultures and attitudes to the reality. Its aim is not, however, to discuss any formal aspects of the text, since such a kind of detailed analysis cannot be the subject of one article only. That is why the article concentrates on the plot of the novel and its possible relations to some actual problems the Finnish society faces. Taking it all into consideration it may be seen as an introduction to a wider analysis of Leena Lehtolainen’s works.